Hippocampal functional connectivity across age in an App knock-in mouse model of Alzheimer's disease - Morrissey, Zachery D.; Gao, Jin; Zhan, Liang; Li, Weiguo; Fortel, Igor; Saido, Takaomi; Saito, Takashi; Bakker, Arnold; Mackin, Scott; Ajilore, Olusola; Lazarov, Orly; Leow, Alex D. (Frontiers in Aging Neuroscience, 2023)
Alzheimer’s disease (AD) is a progressive neurodegenerative disease. The early processes of AD, however, are not fully understood and likely begin years before symptoms manifest. Importantly, disruption of the default mode network, including the hippocampus, has been implicated in AD. To examine the role of functional network connectivity changes in the early stages of AD, we performed resting-state functional magnetic resonance imaging (rs-fMRI) using a mouse model harboring three familial AD mutations (App NL-G-F/NL-G-F knock-in, APPKI) in female mice in early, middle, and late age groups. We observed increased interhemispheric functional connectivity (FC) in the hippocampus across age. This increase was attenuated, however, in APPKI mice in later age. Further, we observed reduced hemispheric asymmetry in FC in APPKI mice. Together, this suggests that there are early changes in hippocampal FC prior to heavy onset of amyloid β plaques, and may be clinically relevant as an early biomarker.